Determination of Polystyrene Layer Thickness and Zinc Phthalocyanine (Znpc) with Modified Sauerbrey Equations and Scanning Electron Microscope (SEM) - Lalu A Didik; Eka Rahmawati; Fadli Robiandi; Susi Rahayu; Abdurrouf Abdurrouf; Djoko H. Santjojo; Setyawan P. Sakti; Masruroh Masruroh (Natural B, Journal of Health and Environmental Sciences, 2014)
The thickness measurement of PS thin films on QCM surface and ZnPc layer on QCM/PS using Sauerbrey equation and Scanning Electron Microscope (SEM) has been investigated. Calculation result using a modified Sauerbrey equation show the thickness of PS layer and ZnPc one are 0,45 μm and  0,0676 μm respectively. Additionally the thickness measurement by using SEM shows the thickness of PS  layer is 5,33 μm and the  thickness of ZnPc layer is 10,44 μm. The differences thickness between Sauerbrey equation and SEM topograph is due to layers porosity. The topography of thin films produced by the secondary electron beam scanning allows to get a magnification of SEM image so that it can be measured directly. While the thickness calculation using the Sauerbrey equation is based on the change in the resonance frequency of QCM.